Reference librarians' perceptions of the issues they face as academic health information professionals - Scherrer, Carol S. (Medical Library Association, 2004)
Background: Leaders in the profession encourage academic health sciences librarians to assume new roles as part of the growth process for remaining vital professionals. Have librarians embraced these new roles? Objectives: This research sought to examine from the reference librarians' viewpoints how their roles have changed over the past ten years and what the challenges these changes present as viewed by both the librarians and library directors. Method: A series of eight focus groups was conducted with reference librarians from private and public academic health sciences libraries. Directors of these libraries were interviewed separately. Results: Reference librarians' activities have largely confirmed the role changes anticipated by their leaders. They are teaching more, engaging in outreach through liaison initiatives, and designing Web pages, in addition to providing traditional reference duties. Librarians offer insights into unanticipated issues encountered in each of these areas and offer some creative solutions. Directors discuss the issues from their unique perspective. Conclusion: Librarians have identified areas for focusing efforts in lifelong learning. Adult learning theory, specialized databases and resources needed by researchers, ever-evolving technology, and promotion and evaluation of the library are areas needing attention. Implications for library education and continuing professional development are presented.